2016
DOI: 10.1093/annonc/mdv576
|View full text |Cite
|
Sign up to set email alerts
|

The effect of real-time electronic monitoring of patient-reported symptoms and clinical syndromes in outpatient workflow of medical oncologists: E-MO AIC, a multicenter cluster-randomized phase III study (SAKK 95/06)

Abstract: Monitoring of patient symptoms, clinical syndromes and their management clearly reduced patients' symptoms, but not QoL. Our results encourage the implementation of real-time monitoring in the routine workflow of oncologist with a computer solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 25 publications
2
107
0
Order By: Relevance
“…It is important to note that patients' symptoms represent a potentially modifiable risk factor that, if properly addressed, may improve health care quality and delivery. Indeed, studies have demonstrated that targeted interventions aimed at improving symptom management can enhance patient‐reported outcomes . However, most of these efforts are targeting the symptom burden of patients with cancer in the ambulatory care setting .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that patients' symptoms represent a potentially modifiable risk factor that, if properly addressed, may improve health care quality and delivery. Indeed, studies have demonstrated that targeted interventions aimed at improving symptom management can enhance patient‐reported outcomes . However, most of these efforts are targeting the symptom burden of patients with cancer in the ambulatory care setting .…”
Section: Discussionmentioning
confidence: 99%
“…Both parameters were chosen on the basis of previous results relating altered circadian rest-activity rhythm to poor outcomes [23,25,27], body weight loss to circadian disruption [24], and both parameters to poor survival outcome on chronotherapy [38]. The proper tracking of the dynamic changes in these parameters entailed the need for daily measurements, whereas other authors have proposed evaluations of symptoms and quality of life once a week or at each clinic visit [4,5,34,35,39,40]. With an overall 59.7% per-protocol compliance rate, and with 95% of the days having at least one data, our study demonstrates the feasibility of cancer patients’ empowerment for gathering and teletransmitting both subjective and objective health-related data.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention arm was associated with a statistically and clinically significant improvement in ESAS symptom distress score (reduction of 5.4 points vs. worsening by 2.1 points, P=0.003). (115)…”
Section: Future Developmentsmentioning
confidence: 99%